Tinjauan Kriminologi Terhadap Penyalahgunaan Narkotika di Kalangan Remaja di Kabupaten Karawang Ditinjau Dari Teori Control Social (Studi Kasus Badan Narkotika Nasional Karawang) - Nurbaliza, Violita; Dewi, Sartika; Abas, Muhamad (UNES Law Review, 2024)
feeling in everything from digestion to pain relief, and lead to dependency. In criminological theory, one of them is studying criminals from a sociological perspective,which is to look for different reasons for the crime rate in the social environment. In connection with the above problems, it can be linked to social control theory relating to sosialigical variables, including structure, family, education and dominant groups. From a sociological standpoint, criminological theory examines, investigates, and discusses the linkages that exist between location, ethnicity, and group membersas long as these ties have the potential to result in criminal activity. Based on the notion of social control and preventative measures against drug misuse among teens, the study seeks to investigate the elements that lead to drug abuse among teenagers, as conducted by BNN Karawang. An empirical juridical approach is used, which is a study of how the law is applied in society. The results of this research show that the factors causing the circulation of narcotics among teenagers in Karawang Regency are unternal factors causing the circulation of narcotics among teenagers in Karawang Regency, namely rehabilitation service efforts, socialization efforts, online media efforts and mitigation efforts by forming villages shining.